Manipulating plasma thyroid hormone levels alters development of endothermy and ventilation in nestling red-winged blackbirds - Sirsat, Tushar S.; Sirsat, Sarah K. G.; Price, Edwan R.; Pineda, Megan; Dzialowski, Edward M. (Frontiers in Physiology, 2022)
Thyroid hormones are key regulators of development and metabolism in vertebrates. During the nestling period, young of altricial species transition from an ectothermic phenotype to an endothermic phenotype. Red-winged blackbirds are an altricial species that exhibit an increase in plasma 3,3’, 5-triiodo-L-thyronine (T3) levels during the first 5 days post-hatch (dph), begin to develop endothermic metabolic responses by 7 dph, and fledge within 10 days of hatching. We propose that thyroid hormones play an important role in regulating development of endothermy during the nestling period in altricial birds. To better understand the effects of thyroid hormones on endothermic metabolic development in an altricial species, we treated nestling red-winged blackbirds on 2, 3, and 5 dph with either methimazole (MMI) to induce hypothyroidism or supplemental T3 to induce hyperthyroidism. We then measured on 5, 7, and 9 dph morphology and whole animal O2 consumption (V̇o2) and ventilation in the thermal neutral zone and during gradual cooling. Treatment of nestlings with MMI resulted in lower plasma T3 levels on 5 dph that recovered by 7 dph, while supplementing with T3 did not affect plasma T3 levels on 5, 7 and 9 dph. Treatment with MMI resulted in smaller nestlings with smaller hearts and structural characters such as wing chord and femur length, but larger lungs and kidneys. Treatment with T3 produced smaller nestlings with smaller body masses and shorter femur and tarsus lengths. The development of V̇o2 and ventilation endothermic responses to gradual cooling in MMI treated nestlings were delayed when compared with control nestlings. In 9 dph nestlings, hypothyroidism resulted in alterations in the responses of ventilation frequency and tidal volume to cooling when compared with the control nestlings. Supplemental T3 had no effect on the development of V̇o2 and ventilation in the thermal neutral zone or in response to cooling. Our data suggest plasma thyroid hormone levels play an active role in the systemic development of endothermic capacity and the development of ventilatory control. In the nestling avian, multiple systems develop in concert to produce an endothermic phenotype, but reduced thyroid hormone delays maturation of endothermic capacity.